A comparison of EBV serology and serum cell‐free DNA as screening tools for nasopharyngeal cancer: Results of the Singapore NPC screening cohort. Issue 10 (8th January 2020) - Tay, Joshua K.; Siow, Chor H.; Goh, Han L.; Lim, Chwee M.; Hsu, Pon P.; Chan, Soh H.; Loh, Kwok S.
Abstract : We aimed to evaluate the effectiveness of nasopharyngeal cancer (NPC) screening by comprehensive clinical follow‐up and adjunctive Epstein–Barr virus (EBV) testing. In a prospective cohort study, 524 individuals with a first‐degree family history of NPC were recruited at a university clinical center in Singapore. The cohort was evaluated at baseline and at 6 monthly intervals, with a complete head and neck examination including nasopharyngeal endoscopy. Blood was taken at baseline and at yearly intervals for EBV Viral Capsid Antigen (VCA) IgA, EBV Early Antigen (EA) IgA serology and serum cell‐free EBV DNA. Nasopharyngeal biopsy was performed when any irregularity in the nasopharynx was observed, or when EBV markers were elevated. The mean duration of follow‐up was 57.7 months, with an average of 8.6 clinical visits per participant. Five participants (0.96%) were identified to have NPC, giving a prevalence of 199 per 100, 000 person‐years of screening. Four of the five NPC cases identified had asymptomatic T1 disease, at an earlier stage compared to NPC patients diagnosed in the clinic during the same time period ( p = 0.0297). All NPC cases identified had elevated EBV‐EA IgA titers ≥1:10, with a specificity of 94.6% and a positive predictive value of 15.2%, outperforming EBV‐VCA IgA and serum EBV DNA. Two NPC cases were biopsied only because of elevated EBV serology titers, with increasing EBV‐EA IgA titers preceding the diagnosis of NPC. In conclusion, screening for NPC is effective in identifying early‐stage disease. Adjunctive EBV‐EA IgA testing improved the effectiveness of screening. Abstract : What's new? In Asian endemic areas, most nasopharyngeal carcinoma (NPC) tumors are associated with Epstein‐Barr virus (EBV) latency. Circulating tumor DNA and serological screening methods have both been used, but they have not been directly compared. Here, the authors present a prospective cohort study of first‐degree family members of NPC patients who participated in a comprehensive screening program. The results show that using a combination of clinical examination and laboratory tests is effective in identifying early‐stage disease. In an asymptomatic high‐risk population presenting predominantly with early‐stage NPC, EBV‐EA IgA serology gave the best sensitivity and specificity profile.